Proportion and Associated Factors of Low Vision among Adult Patients Attending at University of Gondar Tertiary Eye Care and Training Center, Gondar Town, Ethiopia - Melkamu Temeselew Tegegn; Gizachew Tilahun Belete; Ayanaw Tsega Ferede; Aragaw Kegne Assaye (Journal of Ophthalmology)
Introduction. Low vision is a worldwide health problem in both developing and developed countries. A national survey of low vision and blindness in Ethiopia showed that the prevalence of low vision was 3.7% and that of blindness was 1.6%, whereas there is no evidence in the study area. Purpose. The study was aimed to assess the proportion and associated factors of low vision at the University of Gondar tertiary eye care and training center. Methods. A hospital-based cross-sectional study was conducted on 727 study participants with a systematic random sampling technique from April 18 to May 16, 2019. Data were collected through the use of a structural questionnaire and physical eye examination. Data were entered into Epi Info version 7, and analysis was performed by using statistical package for social science (SPSS) version 20. The binary logistic regression model was fitted to identify factors associated with low vision, and variables with a P value of <0.05 in a multivariable binary logistic regression were considered as statistically significant. Results. A total of 715 study participants have participated in this study with a mean age of 49.39 ± 19.93 years. The prevalence of low vision was 35.7% (95% CI: 32.3, 39.3). Being female (AOR = 1.58; 95% CI: 1.10, 2.28), no formal educational level (AOR = 2.24; 95% CI: 1.25, 4.02), history of cataract surgery (AOR = 2.58; 95% CI: 1.53, 4.36), and age ≥ 70 years (AOR: 3.96; 95% CI: 2.21, 7.10) were significantly associated with low vision. Conclusion and Recommendation. The prevalence of low vision found in this study was high as compared with the national and global magnitude. Older age, being female, previous history of cataract surgery, and no formal education were independently and significantly associated with low vision. Cataract and uncorrected refractive errors were identified as the main causes of low vision. Therefore, it requires a plan to provide an eye care education to the community, increasing the quality of cataract surgery and refractive service for the community in the catchment area.